Postoperative customary outcomes and complications after extraction of impacted mandibular third molars and influence of surgery on the adjacent second molar - Zhang, Tian; Liu, Chen (Vojnosanitetski pregled, 2025)
Background/Aim. Extraction of impacted mandibular third molars (IMTMs) may be difficult due to a hidden position, anatomical structure, and limited operating space. Therefore, searching for an effective and safe extraction method has always been the focus of research. The aim of this study was to examine postoperative customary outcomes and complications after the extraction of IMTMs and the possible influence of surgery on the adjacent second molar. Methods. A total of 86 patients with IMTMs, admitted from March 2022 to March 2024, were randomized into two equal groups: the control group (CG) and the study group (SG), each consisting of 43 patients. Traditional IMTM extraction was performed for CG, while piezosurgery was conducted for SG. Clinical indicators, customary outcomes (pain degree, swelling degree, and degree of mouth opening limitation), and complications were compared between the two groups. Results. The pain factor levels and periodontal status of the adjacent second molar were observed pre- and postoperatively. In SG, the operation time was shorter and intraoperative blood loss was less than in CG (p < 0.05). After surgery, the Visual Analogue Scale scores were higher in both groups than preoperatively, but they were lower in SG than in CG (p < 0.05). The degrees of swelling and mouth opening limitation were lower in SG than in CG (p < 0.05). SG had a lower percentage of complications than CG on the 30th day postoperatively (p < 0.05). Conclusion. For IMTM extraction, patients receiving piezosurgery have satisfactory short-term healing outcomes, accompanied by good long-term outcomes of the adjacent second molar.
Keywords: molar; oral surgical procedures; piezosurgery; tooth extraction; tooth, impacted; treatment outcome.